Remission in Crohn’s disease is accompanied by alterations in the gut microbiota and mucins production - Magro, Daniéla Oliveira (Sci Rep, 2019)
Previous studies have demonstrated that patients with Crohn’s disease (CD) in remission do not exhibit an improvement in gut microbiota composition, which might trigger relapses. The present study investigated the dysbiosis and mucins production in CD patients during remission. We performed an analytical cross-sectional single center study, which recruited 18 CD patients and 18 healthy controls (CG) residing in the same home, meaning that all of the participants experienced the same environmental factors, with similar hygiene status, diet, pollution and other common lifestyle characteristics that may influence the composition of the gut microbiota. When compared to healthy controls, the CD patients exhibited lower microbial α-diversity (p = 0.047), a greater abundance of the Proteobacteria phylum (p = 0.037) and a reduction in the Deltaproteobacteria class (p = 0.0006). There was also a reduction in the Akkermansia (p = 0.002) and Oscillospira (p = 0.024) genera and in the proportion of the yeast Saccharomyces cerevisiae (p = 0.01). Additionally, CD patients in remission presented increased neutral (p = 0.001) and acid mucin (p = 0.002) concentrations. The reductions in the proportions of Oscollospira and Akkermansia genera, sulfate-reducing bacteria and Saccharomyces cerevisiae, observed in the CD group, may account for the increased mucins production observed in these patients.